The population dynamics of some arid zone plants during 46 years of grazing on Mileura Station, Western Australia - Davies, Stephen; Kenny, S.; Walsh, T. (2015)
© 2015 Australian Rangeland Society. Grazed quadrats were monitored on Mileura Station, Western Australia from 1967 to 2013 in order to study the population dynamics of the perennial plants in two of the land systems on the property. Counts of plants on four quadrats at each of 10 sites were made in 1967, 1976, 1990 and 2013, and individual plants were traced for the first three samplings. Five sites were on the Sherwood land system and five on the Belele land system. The results indicated that the populations of some species in the mulga shrubland increased steadily over the 46 years of the study whereas the populations of other species, especially the small, short-lived shrubs, fluctuated over this period. A reduction in stocking rate from 1976 to 1990 was associated with an increase in the population of perennial plants; the total numbers for the 1976 count were 1506 compared with 2102 in 1990. Mean summer rainfall increased between 1990 and 2013 and this increase may have been associated with the recruitment. Overall, the study showed that commercial stocking, although at a lower rate than that recommended by the Western Australian Department of Agriculture, was compatible with increases in the populations of the perennial components of mulga shrubland in this region.